THE INFLUENCE OF BRAND TRUST TOWARDS BRAND LOYALTY ON SOFTDRINK CONSUMER (A Study On Teenager’s Consumer Of TehBotolSosro In Malang, Indonesia) - Firlana Rahmania; Radityo Putro Handrito (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to explain the variables brand characteristics, company characteristics, and consumer – brand characteristics of brand trust that influence brand loyalty on teenagers consumer of TehBotolSosro in Malang either partially, simultaneously, and which variable that influence dominantly. The number of respondents are 400 people that taken in 5 sub-districts in Kota Malang. Research instrument used was questionnaire with purposive sampling technique and proportionate stratified random sampling. The analytical method used is multiple linear regression. Based on the results of the analysis, the variables brand characteristics, company characteristics, and consumer – brand characteristics of brand trust simultaneous effect on brand loyalty. Meanwhile, the partial effect, only the variable company characteristics does not have a significant effect on brand trust. The variable consumer brand characteristics effect brand loyalty dominantly. This study showed that brand trust effect on brand loyalty. Keywords : brand characteristics, company characteristics, and consumer – brand characteristics, brand trust, brand loyalty.